2020
DOI: 10.22219/jppg.v1i1.12430
|View full text |Cite
|
Sign up to set email alerts
|

Kesiapan Mahasiswa Pendidikan Profesi Guru (PPG) Dalam-Jabatan untuk Menempuh Program Praktik Pengalaman Lapangan

Abstract: Kualitas sumber daya manusia suatu bangsa berbanding lurus dengan kualitas pendidikannya. Untuk itu, sistem pendidikan yang utamanya berkenaan dengan pendidikan profesi profesi guru menjadi sangat krusial. Dalam konteks ini, pada kondisi mutakhir ini dalam sistem pendidikan di Indonesia digalakkan system yang mengarah pada peningkatan kulaitas guru melalui program Pendidikan Profesi Guru (PPG). Tujuan penelitian ini adalah memperoleh deskripsi mengenai kesiapan mahasiswa PPG dalam menempuh Praktik Pengalaman L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
2
3
0
4
Order By: Relevance
“…This PPG student also illustrates no gender difference in teacher competence. This is in line with Sunaryo, Zuriah [17] research, which states that teacher competence is not influenced by gender but differs according to [21], saying that the female gender has better competence than the male gender. But in this study, it was found that there was no difference in the competence of prospective teachers based on gender.…”
Section: Discussionsupporting
confidence: 90%
“…This PPG student also illustrates no gender difference in teacher competence. This is in line with Sunaryo, Zuriah [17] research, which states that teacher competence is not influenced by gender but differs according to [21], saying that the female gender has better competence than the male gender. But in this study, it was found that there was no difference in the competence of prospective teachers based on gender.…”
Section: Discussionsupporting
confidence: 90%
“…Dalam Pasal 1, diterangkan bahwa program Pendidikan Profesi Guru adalah program pendidikan yang diselenggarakan untuk mempersiapkan lulusan S1 kependidikan dan S1/DIV non-kependidikan yang memiliki bakat dan minat menjadi guru agar menguasai kompetensi guru secara utuh sesuai standar nasional pendidikan sehingga dapat memperoleh sertifikat pendidik profesional pada pendidikan anak usia dini, pendidikan dasar, dan pendidikan menengah. Sejalan dengan itu, kurikulum PPG didesain untuk memberikan kesempatan kepada mahasiswa untuk mendalami dan memantapkan kompetensinya (Sunaryo, Handayani, & Zuriah, 2020), yang meliputi pendalaman materi pedagogik dan profesional, lokakarya penyusunan perangkat pembelajaran, latihan mengajar melalui pembelajaran mikro, dan program pengalaman lapang (PPL). Pada akhir program, para peserta akan mengikuti uji kompetensi mahasiswa PPG (UKMPPG) yang terdiri atas uji pengetahuan (UP) dan uji kinerja (UKin) atau praktik mengajar sebagai prasyarat memeroleh sertifikat pendidik (Pangestika & Alfarisa, 2015).…”
Section: Pendahuluanunclassified
“…Kajian-kajian tersebut umumnya mengeksplorasi analisis butir soal yang disusun oleh guru untuk mengevaluasi kemampuan siswa (Amalia & Widayati, 2012;Kurniawan, 2015;Septiana, 2016;Winata et al, 2014;(Anggreini & Darmawan, 2017) atau analisis butir soal yang disusun oleh mahasiswa dalam perkuliahan (Pantiwati & Permana, 2017). Di sisi lain, kajian terhadap Pendidikan Profesi Guru berfokus pada urgensi pelaksanaan pendidikan profesi guru dalam upaya peningkatan profesionalisme guru (Pangestika & Alfarisa, 2015;Zulfitri et al, 2019) beserta analisis kebijakannya (Disas, 2017), kompetensi mahasiswa PPG (Sunaryo et al, 2020), dan implementasi program PPG (Murdiyanto, 2020;Quddus, 2019). Dengan kata lain, belum ada penelitian yang mendalami tentang analisis butir soal Uji Pengetahuan PPG.…”
Section: Pendahuluanunclassified
“…Previous research on the urgency of development practices and field experience practice innovations is as follows: (1) The need for an innovation, namely designing a field experience practice curriculum management through the formulation of success criteria and learning plans which are intended to be guidelines for civil servant teachers in educating practitioners [5]; (2) The need for the use of an integrated/collaborative management model in the implementation of field experience practices. LPTK's partnership with partner schools is not only at the implementation stage, but since curriculum preparation, implementation, to the stage of reporting on field experience practices [6]; (3) The classroom management strategy requires the teacher's communicative competence in creating and maintaining a classroom atmosphere (condition) so that learning activities can take place efficiently [7]; (4) The importance of technology-based management and design in learning [8]; and (5) The readiness of the practitioner in taking the field experience practice is built on the factors of learning on campus, teaching experience at the home school, and the acceptance of partner schools [9].…”
Section: Introductionmentioning
confidence: 99%